Role of Adrenaline Sclerotherapy for Controlling Upper GI Bleeding (Medical Forum Monthly, 2024)
Objectives:To determine the efficacy of adrenaline sclerotherapy to control upper GI bleedingStudy Design:Observational / descriptive study.Place and Duration of Study:The study was conducted at Gastroenterology/Medical Ward, Lahore General Hospital, Lahore in collaboration with Chandka Medical College Hospital, Larkana from 1st January 2016 to 30th June 2016.Materials and Methods:In this study a total of 100 cases of either gender between 20-60 years of age with upper GI bleed within last 24 hours were enrolled. The basic demographic data including age, gender, clinical presentation were recorded. Clinical efficacy of adrenaline was considered if there was no further upper GI bleeding upto 72 hour after endoscopy.Results: The mean age was recorded as 38.41±11.83 years, 57% (n=57) were males and 43% (n=43) were females, efficacy of adrenaline sclerotherapy in controlling upper GI bleeding in was recorded in 66%(n=66) of the cases.Conclusions:The efficacy of adrenaline sclerotherapy is significantly higher and encouraging for controlling upper GI bleeding and this modality may be used for effective management of upper GI bleeding.